QUALITATIVE COMPONENTS OF CYNICISM IN INDIVIDUALS PERFORMING DUTIES UNDER EXTREME CONDITIONS - Sarbey, Yulia (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2025)
B a c k g r o u n d . The article presents theoretical and methodological approaches to the study of morality among professionals engaged in extreme occupations and manifestations of cynicism in their interactions with others. Empirical data highlight the differences in the expression of qualitative components of cynicism among service personnel of the National Guard of Ukraine with varying levels of combat experience. Law enforcement officers, military personnel, emergency responders, and other professionals involved in combat operations are subject to intense moral and physical strain. The impact of numerous stressors of various origins can result in neuropsychological disorders, psychosomatic illnesses, maladaptive behaviours, chronic tension, decreased productivity, and emotional stress. These effects, in turn, contribute to emotional burnout, disruption of moral attitudes, and in some cases, immoral behaviour. Individuals in high-risk professions must be psychologically resilient to withstand burnout, cognitive distortion, and destructive influences. These realities underscore the scientific necessity for thorough examination of the moral domain of individuals operating in extreme and crisis conditions, as well as the development of effective methods to mitigate the negative effects of professional stressors. M e t h o d s . Theoretical methods included analysis and generalisation of academic literature addressing morality and cynicism in individuals, particularly those working under extreme conditions. The empirical method employed was testing using the "CIN-1 Questionnaire for Qualitative Components of Cynicism." R e s u l t s . A theoretical review was conducted of domestic and international literature on the study of morality and cynicism in professionals working in high-risk occupations. Despite the relevance of the topic – especially in the context of large-scale combat actions in Ukraine – the volume of scientific work exploring its psychological aspects remains limited. The empirical study revealed distinct patterns in the manifestation of qualitative components of cynicism among service personnel of the National Guard of Ukraine. C o n c l u s I o n s . The psychodiagnostic study demonstrated that respondents with combat experience perceive events and phenomena related to cynicism with greater emotional intensity and saturation compared to those without such experience. Respondents with combat experience exhibited a higher level of cynical behavioural tendencies, particularly in relation to law enforcement practices, than their non-combat counterparts. Individuals without combat experience were more inclined to analyse, reflect, and form judgments regarding cynicism. However, both groups showed similar levels of attitudinal components and perception of cynical information encountered in their lives. Future research perspectives include examining the gender-specific expression of cynicism among professionals in extreme occupations and developing strategies for mitigating its harmful effects on personality.